Beyond Chemical Bonding Interaction: An Insight into the Growth Process of 1D ZnO on Few‐Layer Graphene for Excellent Photocatalytic and Room Temperature Gas Sensing Applications. Issue 25 (3rd July 2018) - Rakkesh, R. Ajay; Durgalakshmi, D.; Balakumar, S.
Abstract: A facilechemical synthesis approach is reported for simultaneous reduction of graphene oxide (GO) and chemically planted 1D ZnO Nanorods (NRs) on the few‐layer graphene (FLG) through chemical bonding interaction. The chemically bonded 1D ZnO – few layer graphene nanostructures are investigated by high resolution scanning transmission electron microscopy, photoelectron spectroscopy, X‐ray diffraction and photoluminescence studies. This multifunctional nanostructure efficiently boosts the photocatalytic activity by photodegradation of industrial pollutants within 5 minutes under natural sunlight irradiation and also senses the very low concentration (10 ppm) of hydrogen gas at room temperature with very high sensing response. The emerging photocatalytic performance and the room temperature gas sensing characteristics of 1D ZnO – few layer graphene is attributed to the presence of C–Zn chemical bonds, which plays an essential role in the interfacial charge transfer process between the graphene layers and 1D ZnO NRs. The strong chemical bonding interaction and interfacial charge transfer effects have been experimentally elucidated from the ionization value and work function characteristics of the synthesized hybrid nanostructure. This work demonstrates the simple way of preparing hybrid nanostructure with exposed crystal facets, which could provide an exposure for developing multifunctional nanomaterials towards sensing and removal of hazardous pollutants from our environment. Abstract : We have fabricated chemically bonded 1‐D ZnO nanorods – few layer Graphene based hybrid nanostructures which could be used for multifunctional applications such as reusable highly efficient photocatalyst and hazardous gas sensing material.